The Effect of Switching to Second-Line Antiretroviral Therapy on the Risk of Opportunistic Infections Among Patients Infected With Human Immunodeficiency Virus in Northern Tanzania. (29th January 2016) - Ramadhani, Habib O.; Bartlett, John A.; Thielman, Nathan M.; Pence, Brian W.; Kimani, Stephen M.; Maro, Venance P.; Mwako, Mtumwa S.; Masaki, Lazaro J.; Mmbando, Calvin E.; Minja, Mary G.; Lirhunde, Eileen S.; Miller, William C.
Abstract : The article evaluated effects of switching to second-line ART in contexts where viral load monitoring is not available. Physician's reluctance in switching patients to second-line ART based on CD4+ cell count monitoring was associated with increased risk of opportunistic infections. Abstract: Background.  Due to the unintended potential misclassifications of the World Health Organization (WHO) immunological failure criteria in predicting virological failure, limited availability of treatment options, poor laboratory infrastructure, and healthcare providers' confidence in making switches, physicians delay switching patients to second-line antiretroviral therapy (ART). Evaluating whether timely switching and delayed switching are associated with the risk of opportunistic infections (OI) among patients with unrecognized treatment failure is critical to improve patient outcomes. Methods.  A retrospective review of 637 adolescents and adults meeting WHO immunological failure criteria was conducted. Timely and delayed switching to second-line ART were defined when switching happened at <3 and ≥3 months, respectively, after failure diagnosis was made. Cox proportional hazard marginal structural models were used to assess the effect of switching to second-line ART on the risk of developing OI. Results.  Of 637 patients meeting WHO immunological failure criteria, 396 (62.2%) switched to second-line ART. Of those switched, 230 (58.1%) were delayed. Switching to second-line ART reduced the risk of OI (adjusted hazards ratio [AHR], 0.4; 95% CI, .2–.6). Compared with patients who received timely switch after failure diagnosis was made, those who delayed switching were more likely to develop OI (AHR, 2.2; 95% CI, 1.1–4.3). Conclusion.  Delayed switching to second-line ART after failure diagnosis may increase the risk of OI. Serial immunological assessment for switching patients to second-line ART is critical to improve their outcomes.